Secondary Succession in the Dry Tropical Forests of India: Impact Assessment of Long Term Protection in the Yamuna Ravines - Raizada, A.; Prajapati, M. C.; Bhushan, L. S. (Indian Forester, 2017)
Ravines cover an area of 2.06 m ha and are abundant in areas with alluvial soils, long hot dry summers and average annual rainfall of 750-850 mm along three major rivers - Yamuna, Chambal and the Mahi. These areas are highly disturbed ecosystems and have been overexploited for firewood, fodder and other non-wood forest products leading to degradation. Over the last two decades efforts have been focused on the bio-remediation of degraded lands by providing protection and allowing natural recover processes to rehabilitate the area. This study describes the chronosequence of secondary succession in ravines along the Yamuna, the natural forest cover being described as Northern Tropical Ravine Thorn Forest (6B/C2). Various ecological parameters like richness, concentration of dominance and diversity index were calculated; cluster analysis and multi-axis ordination were carried out to ordinate similar sampling units by considering each year as an independent sampling unit in two micro-catchments of 6 ha each in three topographic situations (ravine top, slopes and bottom). Eleven grass species were recorded, with A.mutica, E.compressa and C. jwarancusa appearing at the site within two years of protection. Nearly forty herbaceous species were recorded, the first appearing after three years. The number of shrub was very low and four species were recorded, with Ziziphus nummularia being regularly recorded at different points of time. No tree species was recorded for twenty years on the ravine hump due to the xeric conditions, while on the slopes and bottom D.sissoo, B.aegyptica and A.nilotica were recorded from the seventh year, with the initial abundance of D. sissoo declining by the 20th year when illicit trespassing became unmanageable.